Voltage-dependent gating of ion channels - Elmslie, Keith S. (Henry Stewart Talks, 2011)
Voltage-dependent ion channels, Critical to proper nerve and muscle function, Voltage sensitivity is mediated by positively charged segments of the protein, These voltage sensors move outward with depolarization to trigger channel opening, The return of one sensor to the resting positions closes the channel, Hypothesized mechanisms of voltage sensor movement are detailed